2013
DOI: 10.1111/lam.12078
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and growth determination of lactic acid-utilizing yeasts from the ruminal fluid of dairy cattle

Abstract: Significance and Impact of the Study: This study demonstrates that yeasts isolated from the ruminal fluid of dairy cattle can utilize lactic acid as a carbon and energy source for growth. The isolated yeasts can be used as probiotic supplements for dairy cattle that are fed highly concentrated diets to reduce ruminal lactic acid production. AbstractRuminal organic acid production, especially lactic acid, can be modified by feeding cattle highly concentrated diets, which have been shown to adversely affect dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…This may be because of the lower WSC content and higher N content of the native grass, or because naturally occurring LAB reduced the effects of the applied inoculants, as proposed by Contreras-Govea and Muck (2012). On the other hand, Sirisan et al (2013) reported that some yeasts could utilize lactic acid as a carbon and energy source. That the LAB strains did not improve the fermentation quality of native grass silage might be explained by the large number of yeasts on native grass (Table 1), with some of them probably being lactic acid-utilizing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because of the lower WSC content and higher N content of the native grass, or because naturally occurring LAB reduced the effects of the applied inoculants, as proposed by Contreras-Govea and Muck (2012). On the other hand, Sirisan et al (2013) reported that some yeasts could utilize lactic acid as a carbon and energy source. That the LAB strains did not improve the fermentation quality of native grass silage might be explained by the large number of yeasts on native grass (Table 1), with some of them probably being lactic acid-utilizing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sirisan et al . () reported that some yeasts could utilize lactic acid as a carbon and energy source. That the LAB strains did not improve the fermentation quality of native grass silage might be explained by the large number of yeasts on native grass (Table ), with some of them probably being lactic acid‐utilizing.…”
Section: Discussionmentioning
confidence: 99%
“…In general, lactic acid was produced during the early stage of ensiling; however, the lactic acid in the large needlegrass silage was not detected until 30 days after ensiling. Sirisan et al () reported some yeasts could utilize lactic acid as a carbon and energy source for growth; the low lactic acid content in large needlegrass silage might be explained by large number of lactic acid‐utilizing yeasts (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mendes et al (2012) reported P. kudriavzevii as the most abundant yeast in isolates from ruminal samples from dairy cattle fed tropical forages. The genus Pichia was also isolated from the rumen of dairy cows (Sirisan and Pattarajinda, 2011;Sirisan et al, 2013) using a PCR approach to amplify the D1/D2 domain of 26S rDNA.…”
Section: Resultsmentioning
confidence: 99%
“…They proposed that yeast removed the oxygen in the rumen, promoting anaerobic microorganisms' development, and therefore enhance fiber digestion. The positive effects of yeast in the ruminal environment could also be due to the interaction of yeast with the rumen microorganisms, stimulating certain microbial population with its consequent effect (Sirisan et al, 2013;Marrero et al, 2015). Mendes et al (2012) suggested that yeasts are able to degrade simple carbohydrates, which could favor the growth of yeast populations, and also contribute to the regulation of ruminal pH.…”
Section: Resultsmentioning
confidence: 99%